Tháng Năm 19, 2024

Dùng tính chất cơ bản của phân thức, hãy tìm các đa thức trong mỗi đẳng thức sau: a) \(\frac{{{x}^{2}}-4x+4}{4-{{x}^{2}}}=\frac{2-x}{A}\) b) \(\frac{-{{x}^{2}}+6xy-9{{y}^{2}}}{x+3y}=\frac{B}{{{x}^{2}}-9{{y}^{2}}}\) c) \(\frac{{{x}^{2}}+x-6}{({{x}^{2}}-2x)(x+2)}=\frac{x+3}{C}\)

Dùng tính chất cơ bản của phân thức, hãy tìm các đa thức trong mỗi đẳng thức sau:

a) \(\frac{{{x}^{2}}-4x+4}{4-{{x}^{2}}}=\frac{2-x}{A}\)

b) \(\frac{-{{x}^{2}}+6xy-9{{y}^{2}}}{x+3y}=\frac{B}{{{x}^{2}}-9{{y}^{2}}}\)

c) \(\frac{{{x}^{2}}+x-6}{({{x}^{2}}-2x)(x+2)}=\frac{x+3}{C}\)

Lời giải chi tiết:

Hướng dẫn giải chi tiết

\(\begin{align}& a)\,\,\frac{{{x}^{2}}-4x+4}{4-{{x}^{2}}}=\frac{2-x}{A} \\ & \frac{{{x}^{2}}-4x+4}{4-{{x}^{2}}}=\frac{{{(x-2)}^{2}}}{(2-x)(2+x)}=\frac{{{(2-x)}^{2}}}{(2-x)(x+2)}=\frac{2-x}{x+2} \\ & \Rightarrow \frac{2-x}{x+2}=\frac{2-x}{A} \\\end{align}\)

Vậy \(A=x+2\).

\(\begin{align} & b)\,\,\frac{-{{x}^{2}}+6xy-9{{y}^{2}}}{x+3y}=\frac{B}{{{x}^{2}}-9{{y}^{2}}} \\ & \frac{-{{x}^{2}}+6xy-9{{y}^{2}}}{x+3y}=\frac{-({{x}^{2}}-6xy+9{{y}^{2}})}{x+3y}=\frac{-{{(x-3y)}^{2}}}{x+3y}=\frac{-{{(x-3y)}^{2}}.(x-3y)}{(x+3y)(x-3y)}=\frac{-{{(x-3y)}^{3}}}{{{x}^{2}}-9{{y}^{2}}} \\ & \Rightarrow \frac{-{{(x-3y)}^{3}}}{{{x}^{2}}-9{{y}^{2}}}=\frac{B}{{{x}^{2}}-9{{y}^{2}}} \\\end{align}\)

Vậy \(B=-{{(x-3y)}^{3}}\).

\(\begin{align} & c)\,\,\frac{{{x}^{2}}+x-6}{({{x}^{2}}-2x)(x+2)}=\frac{x+3}{C} \\ & \frac{{{x}^{2}}+x-6}{({{x}^{2}}-2x)(x+2)}=\frac{{{x}^{2}}+3x-2x-6}{x(x-2)(x+2)}=\frac{x(x+3)-2(x+3)}{x(x-2)(x+2)}=\frac{(x-2)(x+3)}{x(x-2)(x+2)}=\frac{x+3}{x(x+2)} \\ & \Rightarrow \frac{x+3}{x(x+2)}=\frac{x+3}{C} \\\end{align}\)

Vậy \(C=x(x+2)\).